(untitled) (American International Journal of Economics and Finance Research, 2019)
This paper examined the effects of revenue mobilization and investment on basic amenities of local government in Nigeria. Secondary data were collected from the Central Bank of Nigeria Annual Statistical Bulletin from 1993- 2017. Investment in basic amenities was proxy by monetary value of basic amenities while revenue mobilization was proxy by federal government allocation, state government allocation, value added tax, internally generated revenue and grants to local governments in Nigeria. Ordinary Least Square (OLS), Augmented Dickey Fuller Test, Johansen Co-integration test, normalized co-integrating equations, parsimonious vector error correction model and pair-wise causality tests were used to conduct the investigations and analysis. The empirical findings based on the models found that value added tax, internally generated revenue and grant have negative and significant effect on investment on basic amenities while federal allocation and state allocation have positive effect on the value of basic amenities. The unit root result (ADF) showed that the variables were stationary at the first difference of Order 1 (1). The co-integration tests revealed a long run dynamic relationship between the dependent and independent variables in the models. The parsimonious model summary shows that accounting bases explains a strong and positive significant relationship between the dependent and independent variables. However, the direction of causality between the accounting bases treasury management is mixed indicating uni and bi-directional causality. The study concludes that local government revenue has significant effect on investment of basic amenities of Nigeria local governments.